INVESTIGATING PRE-SERVICE MATHEMATICS TEACHER CRITICAL THINKING ABILITY - Basri, Hasan; Purwanto, Purwanto; As'ari, Abdur Rahman; Sisworo, Sisworo (Universitas Negeri Malang, 2018)
This research aims at investigate the critical thinking ability of pre-service mathematics teacher at Madura University. The instrument used in this research was using the Watson-Glaser Test with the mathematics content. There was 48 pre-service teachers who participated as the subjects in this research. This research used statistic descriptive method to identify the profile of critical thinking ability of pre-service mathematics teacher. The scores from each sub-skill and the total score were calculated to identify the profile of critical thinking ability of pre-service mathematics teacher. Based on the data analysis, it was found out that the critical thinking ability of pre-service mathematics teacher was in the intermediate level, yet deduction sub-skill became the best pre-service mathematics teacher?s critical thinking ability and recognition of assumption skill became the lowest pre-service mathematics teacher?s critical thinking ability.